Inflation Dynamics in Indonesia: Equilibrium Correction and Forward-Looking Phillips Curve Approaches - Insukindro, Insukindro; Sahadewo, Gumilang Aryo (Gadjah Mada International Journal of Business, 2010)
A series of relatively high inflation characterize Indonesian economy, especially during the economic crisis. Economists generally agree that high inflation is one of the major economic problems, and that economic authorities need to cope with such a problem. Therefore, it is essential to understand the behavior of inflation in Indonesia. The aim of this paper is to estimate the inflation dynamics in Indonesia using equilibrium correction and forward-looking Phillips Curve approaches. Previous empirical studies show that the equilibrium correction or backward-looking approach may explain the inflation dynamics in Indonesia. The backward-looking specification does not have to be the proper model even if the fact shows that the specification holds. The major innovation of this paper is the application of a forward-looking Phillips curve model. The empirical resultsâestimated using the Generalized Method of Moments (GMM)âshow that the forward-looking Phillips Curve approach dominates the backward-looking behavior. It indicates that after a credible monetary policy announcement, for instance, the former model predicts that economic agents will change their behavior quickly. Therefore, the policy will affect the economy more rapidly